Electromagnetic surface waves : a modern perspective - Polo, John A.; Mackay, Tom G.; Lakhtakia, A. (Akhlesh), 1957- (Elsevier insights., 2013)
For decades, the surface-plasmon-polariton wave guided by the interface of simple isotropic materials dominated the scene. However, in recent times research on electromagnetic surface waves guided by planar interfaces has expanded into new and exciting areas. In the 1990's research focused on advancing knowledge of the newly discovered Dyakonov wave. More recently, much of the surface wave research is motivated by the proliferation of nanotechnology and the growing number of materials available with novel properties. This book leads the reader from the relatively simple surface-plasmon-pola